Acceleration of acid mine drainage generation with ozone and hydrogen peroxide: Kinetic leach column test and oxidant propagation modeling. (1st January 2022) - Gomes, Thauan; Angioletto, Elidio; Quadri, Marintho Bastos; Cargnin, Maykon; de Souza, Hilária Mendes
Graphical abstract: Highlights: Ozone and hydrogen peroxide can be used to mitigate acid mine drainage formation. Coal mining tailings exhibited reduced sulfur content when oxidants were applied. Ecotoxicity of acid mine drainage decreased after treatment. Effective transport distance of oxidants depends on the saturation of the tailings. Kinetics, modeling, and experimentation established propagation of oxidants. Abstract: Uncovered mine tailings may result in environmental stresses such as severe acidification and heavy metal discharge to adjacent watercourses. These problems originate in metal sulfide oxidation, which results in acidic metal-rich leachate, known as acid mine drainage (AMD) that persists over time. Sulfides in mine tailings can persist for centuries. Thus, accelerating the sulfur oxidation process can help mitigate this problem. In this study, the use of ozone and hydrogen peroxide to increase the leaching of coal mine tailings was investigated in detail. One of the biggest challenges when using oxidizers is determining the acting plume. To this end, the decomposition kinetics of oxidants were studied when contacting mine tailings. Additionally, a mathematical model was developed to predict the subsurface propagation of the oxidizers used. In the group where ozone was applied, there was a 62% reduction in sulfur content, while the corresponding reduction in the control group was only 18%. The results indicated that ozone and hydrogen peroxide increased metal leaching, and decreased ecotoxicity compared to a control group. The kinetic rates were dependent on the saturation of coal mine tailings. Furthermore, the spread model contributed to oxidation plume determination. For ozone, it was observed that for a kinetic rate of - 0.2669 ∙ C O 3 0.7899 mol·m −3 ·s −1, a 60% increase in pressure causes the ozone plume to increase the effective transport distance by 30%. This paper presents an innovative strategy for mitigating AMD.